Investigation of the survivorship needs of patients with primary brain tumours and the provision of a health & wellbeing event. (31st January 2018) - Emerson, Julie; Robson, Sara; Molloy, Liz; Smith, Charlotte; Gilston-hope, Alison; Cundliffe, Sarah; Wadeson, Andrea; McBain, Catherine
Abstract: BACKGROUND: Improvements in treatment mean that the number of people living with a brain tumour is increasing. Survivorship needs are diverse. We undertook a project to introduce routine Holistic Needs Assessment (HNA) and use the issues identified to inform the design of a survivorship event. METHODS: Every patient newly-diagnosed with a primary brain tumour January-June 2016 was offered a 48-item neuro-oncology HNA at diagnosis and on completion of initial treatment, unless deemed clinically inappropriate. Patients ranked concern for each item from 1(low)-10(high). Two thresholds (>4&>7) were used to identify percentages of specific concerns. Data was analysed by tumour type/grade and changes over time. The most prevalent concerns were addressed in a targeted H&WB event. RESULTS: 154 new patients were referred to the service; 104 (68%) completed an HNA at diagnosis. These comprised: Grade IV:55, Grade III:8, Grade II:12, Meningioma:26, Other:3. 49 patients (47%) also completed a post-treatment HNA (Grade IV:36, GIII4, GII:4, Meningioma:5). There was no evidence that needs varied significantly with grade or histology. Highest ranking baseline needs were: fatigue:26%, worry/fear/anxiety:23%, fear of recurrence:22%, transport/driving:21%, mobility:17%. Post-treatment, highest-scoring concerns included sleep and appearance: fatigue:35%, fear of recurrence:27%, mobility:21%, sleep:19%, appearance:19%. Routine HNA completion proved feasible, although sometimes challenging due to time and room availability. The tool identified unreported needs; resulting conversations were valuable. 'Sexuality' was identified as an omission. A Health & Wellbeing event, based on identified needs, was attended by 50 patients and carers. Feedback was positive with high levels of 'usefulness' reported, although the duration of the day proved difficult for some with fatigue and cognitive changes. CONCLUSIONS: Routine HNA use in an unselected patient population proved feasible and valuable, if challenging. The resulting H&WB event was successful; further events are planned. Repeat HNAs later in the disease journey are required to determine how needs change.